Microhabitat use by Peucetia flava (Oxyopidae) on the glandular plant Rhyncanthera dichotoma (Melastomataceae) - Morais-Filho, Jose Cesar [UNESP]; Romero, Gustavo Guevedo [UNESP] (Amer Arachnological Soc, 2008)
Several studies have reported that plant structural components can exert influences on the density and distribution of spiders. However, little is known about which plant traits mediate specific associations between spiders and plants. In southeastern Brazil, the lynx spider Peucetia flava Keyserling 1877 (Oxyopidae) is commonly found on the plant Rhyncanthera dichotoma (Melastomataceae), a shrub that bears glandular trichomes. In this study we investigated if Peucetia occurs strictly on Rhyncanthera and what plant parameters influence the spiders distribution. In addition, we recorded the vertical distribution of spiders of different ages in the plant canopy. Throughout the year Peucetia was observed only on the glandular plant Rhyncanthera, indicating that this association is specific and predictable. Statistical analysis showed no difference in the number of spiders between plants of Rhyncanthera with and without flowers, suggesting that this specific association is mediated by the presence of glandular trichomes, and not by reproductive structures. The distribution of Peucetia over the year was related to the number of arthropods on plants, as well as the number of leaves and height of the host plants, indicating that Peucetia probably choose sites of high food availability. Adults and subadults occurred on higher places on the crown than young and juveniles.
Keywords: Plant architecture; glandular trichomes; spider-plant interactions